La docencia universitaria y los procesos de evaluación de los aprendizajes, propuesta de una guía alternativa con estrategias de evaluación para la carrera de Ingeniería de Medio Ambiente de la Universidad Técnica de Cotopaxi durante el período 2012 - 2013 - Cayo Lema, Luis Efraín (2013)
The teacher’s evaluation guide was made in order to give the Technical University of Cotopaxi Environment Engineering career as a tool that help to improve the management of education in the area related to teaching, especially for all people who have an important place in achieving goals as teachers, the same that is designed to have knowledge and understanding of teaching practice and with this create conditions for the development and continuous improvemen.